A debreceni Tisza István-Tudományegyetem Orvostudományi Karának közreműködése levente egészségügyi tanfolyamok megszervezésében – Jeney Endre professzor javaslata 1937-ből - Mudrák, József (Gerundium, 2015)
THE INVOLVMENT OF MEDICAL FACULTY OF THE TISZA ISTVÁN UNIVERSITY IN THE ORGANIZATION OF MEDICAL COURSES FOR PALADINS – THE SUGGESTION OF PROFESSOR ENDRE JENEY FROM 1937. At the end of 1936 Elemér Vargha, Deputy Mayor of Debrecen, who was the city representative of the Hungarian Red Cross, contacted first the Faculty of Medicine of the Tisza István University to teach medical courses for paladins. Endre Jeney, the professor of economics prepared a detailed plan for two diferent age groups for 12–12 course periods. he detailed plan includes the description of course subjects, provides the schedule, the names of teachers and nurses. At the end, the course was not realized.